(3RHOI GdMdH ef JGQjN MdHs - (3GHi MaU ceGd GdOjf YeQ Hf CMeO Hf gHI Gddg Hf CHi LQGOI GdYbjdi GdMdHj GdeYQha H GHf GdYOjes; (3ceGd GdOjf YeQ Hf CMeO Hf gHI Gddg Hf CHj LQGOI GdYbjdj GdMdHj, CHj MaU , GdeYQha HGHf GdYOje,J (B660 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ebdH GdCehQ hHYO aEf HYV ef jJYjf Ydi GeJKGd CeQg GdJeS ef JYdjb eG hbY Edi ef PcQ EeQGA MdH s
(3BNQgG (B:s
(3hGfgRe edc GdQhe ai Gddjd djdI GdLeYI hYGK GdJQceGf ai CWQGa GdQhe hfgHhG ef NQL Edi GdTGe hgPG BNQ eG hLO HNWg s
(3HChdgG Jedc eDQN ai (B878s
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSNI CNQi HQbe (B691 (3JGQjNs
(3cJHJ ef fSNI cJHJ ef fSNI HNW eDdagG s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs